Refugee education : integration and acceptance of refugees in mainstream society - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2018)
This volume examines how universities and colleges are working towards implementing various interventions to integrate refugees along with non-governmental organizations and local governments to achieve an optimal level of integration with host communities. The first part of the volume addresses the challenges of educating and integrating refugee populations, while the second part considers methods for establishing support systems. Using case studies and other empirical research, this volume presents a broad and in-depth overview of the various methods implemented to integrate the refugees into society.The international case studies revealthe complexity of the perception-practice dynamic and the multi-faceted factors that influence various levels of integration.